Chemoembolization for hepatocellular carcinoma fed by right internal thoracic artery. Issue 45 (November 2017) - Shen, Tao; Jia, Zhongzhi; Huang, Yuanquan; Li, Shaoqin; Jiang, Guomin; Cheng, Lihua
Abstract : Abstract: The purpose of the study was to evaluate the value of transarterial chemoembolization (TACE) via right internal thoracic artery (RITA) for patients with unresectable hepatocellular carcinoma (HCC). From January 2000 to June 2016, a retrospective study was conducted of all patients with unresectable HCC who underwent TACE via RITA across 3 medical centers. The technical success, serum alpha-fetoprotein (AFP) level changes, major complications, disease control rate, and survival were evaluated and analyzed. During the study peroid, in all, 21 patients (men 21; mean age 57.3 ± 7.1 years) were included in this study. Of the 21 patients, all the tumors were located under the capsule of the liver and adjacent to the diaphragm with median tumor diameter of 8.2 cm in 20 patients, and the tumor was located at the surface of the liver due to incisional site metastasis in 1 remaining patient. Lesions fed by the RITA were demonstrated during initial TACE in 2 patients and during repeat TACE therapy in 19 patients. The technical success rate was 100%. The AFP response 1 month after treatment was complete (n = 4) and partial (n = 9) of 13 patients whose AFP was abnormal before the procedure, and the serum levels of AFP reduced significantly 1 month after treatment (1240.1 ± 347.1 vs 175.2 ± 71.8; P  < .01). No major complications occurred. The disease control rate was 100% at 3 months after treatment. The median overall survival from the time of TACE therapy via the RITAs was 18.2 months, and 1-year survival after TACE therapy via the RITAs was 76.2%. Chemoembolization via the RITA can improve the therapeutic efficacy of TACE and reduce the presence of residual HCC.